2011
DOI: 10.4314/ijest.v3i1.67644
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic response of fly ash reinforced functionally graded rubber composite sandwiches - a Taguchi approach

Abstract: The dynamic analysis of jute-epoxy sandwiches with fly ash reinforced functionally gradient (FG) flexible, compliant rubber core is presented. FG samples are prepared using conventional casting technique. Presence of gradation is quantified by weight method. An attempt is made to study the influence of fly ash weight fraction, jute orientation and core to total thickness (C/H) of sandwich on damping ratio (DR) and natural frequency (NF). The design of experiments based upon L9 (3 3) orthogonal arrays by Taguch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(6 citation statements)
references
References 88 publications
0
5
0
Order By: Relevance
“…Deepthi et al [10] studied High Density Poly Ethylene (HDPE)/cenosphere FA composites using maleate ester modified HPDE; they reported improvement in mechanical and thermal properties and decrease in crystallinity. Jute-epoxy sandwiches reinforced with FA to make functionally gradient (FG) composites were prepared by Doddamani et al [11]; they derived a correlation between FA content and their mechanical properties using a Taguchi design of experiments.…”
Section: Introductionmentioning
confidence: 99%
“…Deepthi et al [10] studied High Density Poly Ethylene (HDPE)/cenosphere FA composites using maleate ester modified HPDE; they reported improvement in mechanical and thermal properties and decrease in crystallinity. Jute-epoxy sandwiches reinforced with FA to make functionally gradient (FG) composites were prepared by Doddamani et al [11]; they derived a correlation between FA content and their mechanical properties using a Taguchi design of experiments.…”
Section: Introductionmentioning
confidence: 99%
“…Frostig and Thomsen [25][26][27] investigated the thermal and the thermomechanical nonlinear response of a flat sandwich panel with a compressible core. These papers revealed that the transverse flexibility of the core along its extension and compression as a result of the thermally induced deformation plays a major role in Downloaded by [University of Chicago Library] at 04: 15 19 November 2014 ACCEPTED MANUSCRIPT ACCEPTED MANUSCRIPT 4 the nonlinear response of sandwich panels. The nonlinear behavior of thermally loaded curved sandwich panels with transversely flexible core is developed by Frostig et al [28].…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…M. R. Doddamani, et.al. [6] studied the dynamic analysis of jute-epoxy sandwiches with fly ash reinforced functionally gradient (FG) flexible, compliant rubber core is presented. By using conventional casting technique, a sample of FG was being prepared.…”
Section: IImentioning
confidence: 99%